Encountering the medieval in modern Jewish thought - Diamond, James Arthur; Hughes, Aaron W., 1968- (Supplements to The journal of Jewish thought and philosophy, 2012)
How does the "medieval" function as a bearer of Jewish identity in a changing secular world? Each chapter in Encountering the Medieval in Modern Jewish Thought addresses a different Jewish return to the medieval by using a language of renewal.